Improving Student Learning Outcomes Through the Index Card Match Method in PAIBP Learning Material Asmaul Husna - Sariwati, Nova; Huda, Syamsul; Yusuf, Moh. Asror; Fanani, Moh. Zainal (Proceeding International Conference on Education, 2023)
This Classroom Action Research was carried out in class VI at Madrasah Ibtidaiyah Ma`arif Syuhada Ponorogo. With the background that researchers saw the potential to improve student learning outcomes on the Qur`an Hadits material of Surah Ad-Duha. Due to situations that require the use of technology in learning and demands for teaching and learning activities that are increasingly developing, teachers' teaching abilities using card sort must be improved following existing developments. Educators are expected to be able to utilize learning media as a support for teaching and learning activities to create interactive learning for students so as to increase students' understanding in receiving learning which will influence learning outcomes.